Mixed Monolayer of Amphiphilic Schiff Base of ortho-Vaniline and Stearic Acid: Isotherms and Thermodynamic Properties - Siji Sudheesh; Jamil Ahmad; Girija Shankar Singh (Orbital: The Electronic Journal of Chemistry, 2018)
Surface pressure-area isotherms of pure 2-methoxy-6-[(n-octadecylimino)methyl]phenol (MODIMP) and its mixture with stearic acid are reported.  While the monolayer of pure MODIMP is unstable, mixing it with stearic acid stabilizes and condenses it. As the proportion of stearic acid in the solution being spread increases, the monolayer gets progressively more condensed and the surface pressure-area isotherm shows a decreased compressibility. Values of excess area per molecule of the mixed monolayer compared to the individual components give an indication about the possible interactions between the molecules of the two components and their orientation at the interface.  At lower surface pressures, interactions between the molecules of different components are stronger than those in the pure monolayer, while opposite is the case at higher surface pressures.DOI: http://dx.doi.org/10.17807/orbital.v10i2.1078